2021
DOI: 10.1007/s40820-021-00718-z
|View full text |Cite
|
Sign up to set email alerts
|

Green and Near-Infrared Dual-Mode Afterglow of Carbon Dots and Their Applications for Confidential Information Readout

Abstract: Near-infrared (NIR), particularly NIR-containing dual-/multi-mode afterglow, is very attractive in many fields of application, but it is still a great challenge to achieve such property of materials. Herein, we report a facile method to prepare green and NIR dual-mode afterglow of carbon dots (CDs) through in situ embedding o-CDs (being prepared from o-phenylenediamine) into cyanuric acid (CA) matrix (named o-CDs@CA). Further studies reveal that the green and NIR afterglows of o-CDs@CA originate from thermal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 53 publications
1
63
0
Order By: Relevance
“…[5,6] Currently, anti-counterfeiting labels based on fluorescent patterns have been widely used in various areas around the world. [3][4][5][6][7][8] However, the traditional fluorescent labels can be readily copied or imitated, which are facing rampant counterfeiting phenomena and already cannot meet anti-counterfeiting demands. Therefore, developing advanced anti-counterfeiting technologies with improved security is imperiously demanded.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] Currently, anti-counterfeiting labels based on fluorescent patterns have been widely used in various areas around the world. [3][4][5][6][7][8] However, the traditional fluorescent labels can be readily copied or imitated, which are facing rampant counterfeiting phenomena and already cannot meet anti-counterfeiting demands. Therefore, developing advanced anti-counterfeiting technologies with improved security is imperiously demanded.…”
mentioning
confidence: 99%
“…[11] Moreover, the information is encrypted by multidimensional parameters, such as wavelength, [12][13][14] luminescent lifetime duration, [15,16] phase [17] and polarization. [18] Carbon dots (CDs), [7,8] halide perovskites, [19][20][21][22] organic dyes, [4] semiconductor quantum dots [23] and nanoparticles [24][25][26] are promising luminescent materials for anti-counterfeiting owing to their superior photoluminescence (PL) intensity [27] and tunable PL behaviors. [28,29] For example, Zhang et al reported that the PL of perovskite nanocrystals encapsulated in lanthanide-based metal-organic frameworks (Ln-MOFs) can be quenched by water treatment, and recovered by adding CH 3 NH 3 Br solution, which realized the repeated fluorescent anti-counterfeiting.…”
mentioning
confidence: 99%
“…The syntheses of m-CDs, m-CDs@CA, and experimental cyanuric acid (i.e., eCA) were referenced in our previous reports 28 , 49 . The co-crystallized composite (i.e., m-CDs#CA) was prepared according to a literature method 47 .…”
Section: Methodsmentioning
confidence: 99%
“…Among them, o-phenylenediamine (oPD) is one of the most important precursors to CDs due to its self-doping (i.e., N doping) behavior and low cost. oPD molecules have a conjugated structure and serve as both carbon and nitrogen sources, which are the key elements for PL centers 9 , 10 . Initially, only a variety of blue, green, and yellow emissive CDs with high PLQYs were prepared using oPD as the precursor 11 13 .…”
Section: Introductionmentioning
confidence: 99%